AN EMPIRICAL ANALYSIS OF TAX REVENUE BUOYANCY IN JAMMU AND KASHMIR - Mohd Aasif Bhat; Mohd Rafiq Khan (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
Abstract Taxation is a powerful instrument to finance the deficits of a country. Buoyancy of Tax is a degree of the sensitivity of tax incomes to economic growth. tax is said to be buoyant when revenues increase by more than one percent for a one percent rise in outputor national income (Audi, M. et. al. 2021). This paper is an attempt to examine the buoyancy of Tax revenue of J&K. The data is of time series nature covering the period from 2000- 01 to 2019-20 entirely relies on the secondary sources. The Augmented Dickey-fuller test has been used to check the unit root of the data. Ordinary least square method of regression has been used to estimate the buoyancy of tax revenue in Jammu and Kashmir. The results show that the buoyancy of all the major taxes is less than 1 except for other taxes(other taxes include many taxes).The implication is that the tax system did yield a less than 1 percent change resulting from economic activity, for every 1 percent change in GDP.